Penggunaan Metode Weighted Product Untuk Seleksi Mahasiswa Penerima Beasiswa - Daud, Muhammad Isa; Mufty, Mufty (MEANS (Media Informasi Analisa dan Sistem), 2020)
Making the right decision is very important in a management, wrong decision making can be fatal for both companies and individuals Through the Education Office the government seeks to allocate funds to provide scholarships to students who are economically unable to finance their education and provide scholarships to students who have achievements. In order for the implementation of scholarships to be achieved, it must be in accordance with the principle of 3T, namely On target, Right amount and On time. The provision of tuition fee assistance in the form of scholarships is also given to students in universities. Scholarships are given to students who excel and are underprivileged. The selection of scholarship recipients so far is not maximal because of the assessment that seems to favor one student so that students who really deserve it become unable to get. In this research using Weighted Products method to conduct the assessment process and the process implemented into a system, it is expected that with the system of decision-makers can choose students who really deserve. The results showed that Mahasiswa 4 was selected as a scholarship student with a score of 0.237